RANCANG BANGUN ROBOT MANUAL PENGANGKAT DAN PEMINDAH BARANG BERBASIS MIKRO KONTROLER AT89S52 - Yordan Hasan (Universitas PGRI Palembang, 2011)
ABSTRACTIn the current era of the times, all aspects of human life has been progressing very rapidly. This development was accompanied and supported by technological developments very, very instrumental in the progress in all areas.Robotic lifting and transfer of goods based microcontroller AT89S52 is one example of the application of electronic systems in the real world and as an example of the technological developments of modern dizaman this. Here theauthors focus on a system controller or controllers on a robot arm transport and transfer of goods. The controller is controlled by a switch located on the joystick and the input to the microcontroller AT89S52 in which there is an assemblerlanguage program whose output can output a voltage that controls the dc motor driver H-Bridge to control the robot arm movement is driven by a dc motor. Switches used to connect to four ports on the microcontroller Port 1.2 to Port 1.5, and the outputs are connected to a dc motor driver H-Bridge located on Port 2.0 to Port 2.5. This output will control the motor so that the robot arms can clamp and remove the clamps, and the robot arm can go up and down, inaccordance with the input control switches located on the joystick the robot.Keywords : Microcontroller AT89S52, Robot Controller, Switch, Driver H-Bridge dc